Continuous and Real-Time Vibration Data Acquisition and Analysis System Based on S3C6410 and Linux - Huangcheng Guo; Huabing Yu; Changyu Sun; Zhibo Zhang; Enming Zheng (2013 Fifth International Conference on Measuring Technology and Mechatronics Automation, 2013)
A new vibration analyzing system based on the S3C6410, a 16/32-bit ARM 11 CPU and the AD7606, an 8-channel high-speed simultaneous 16-bit analog to digital converter (ADC) is presented. The design of hardware is described, in which the IDT72V265, a 16K x 18-bit synchronous FIFO was applied to realize the continuous and real-time data transmission from ADC output register to SDRAM through the data bus of S3C6410. Embedded Linux 3.0 operating system was transplanted, and hardware drivers which provide up-layer Linux applications the interface of ADC control and data transmission have been developed. In the upper computer, the MFC application with functions to receive, save, process and display data from the lower acquisition system was fulfilled. The test results showed that acquisition data was accurate and the system turned out to be reliable at the highest sampling rate of AD7606.